Influence of Decentralisation Factors on Sustainability of Community Development Programmes in Osun and Kwara States, Nigeria (2013)
The quest for decentralisation rests on the capacity to enhance grassroot participation in development programmes and community integration to facilitate even spread of developmental projects. In spite of the adoption of the decentralisation strategy, the physical and socio- economic conditions in most of these communities in Kwara and Osun states do not seem to have improved significantly. Previous studies had focused more on impacts of decentralisation on ethnic conflicts and secessionism rather than on implementation and sustainability of community development. This study, therefore, investigated the influence of decentralisation factors (grassroot participation in development programmes, need for unity, community integration, devolution of power, delegation of authority, development equity and easiness of decision-making process) on sustainability of community development programmes in Osun and Kwara states, Nigeria. The survey research design of ex post facto type was adopted. The stratified random sampling technique was adopted to select 1,984 respondents (community leaders 266; change-agents 569; members of community based organisations 1,022; political representatives 127) in nine communities each from Osun (964) and Kwara states (1,020). Two instruments: Decentralisation Factors’ Scale (r =0.87) and Community Development Sustainability Questionnaire (r =0.76) were used. These were complemented with 18 sessions of Focus Group Discussions (FGD) and Key Informant Interviews (KII) with residents and change-agents. Two research questions were answered and two hypotheses tested at 0.05 level of significance. Data were analysed using Pearson’s Product Moment Correlation, t-test, multiple regression and content analysis. Decentralisation factors significantly correlated (R = .554) with sustainability of community development programmes (F (7, 1975) =125.152; p< 0.05) and accounted for 31% variance in the dependent measure. Relative contributions to sustainability of community development programmes were as follows: unity (β =.710), grassroot participation in development programmes (β=.453), delegation of authority (β =.304), devolution of power (β =.103), community integration (β = .-065), easiness of decision-making (β = .-265) and development equity (β= .-661). No significant difference was found in sustainability of community development programmes through decentralisation between Osun and Kwara states. However, taking the two factors together, Kwara State (= 20.37) performed better than Osun State (= 20.33). Furthermore, political instability (r =453; p< 0.05), leadership problems (r = -230; p< 0.05), communal clashes (r =.136, p< 0.05), inadequate funding (r = 129; p< 0.05) and poor accountability(r =.121; p< 0.05), all impeded the influence of decentralisation factors on the sustainability of community development programmes in the two states. FGD and KII results revealed that there are problems of communication gap and lack of adequate understanding of the basic principle of the decentralisation process among the inhabitants. These have hindered the expected level of citizen participation in developmental projects arisen from decentralisation process. Decentralisation factors enhanced sustainability of community development programmes in Osun and Kwara states and served as potent instruments for programmes. However, the problems of political instability, leadership, inadequate funding, communal clashes, accountability, and communication gap should be considered when planning community development programmes. Besides, there is the need for the provision of community education.